Long-term survival in patients with pancreatic cancer treated with second-line liposomal irinotecan plus 5-fluorouracil/leucovorin: observations from Korea, Italy, and Germany - S. Lonardi; K. Potthoff; L. Procaccio; C. Yoo; T. Macarulla; F. Hedouin-Biville; G.W. Prager (ESMO Gastrointestinal Oncology)
Pancreatic cancer (PAC) is an aggressive disease with poor clinical outcomes. Liposomal irinotecan in combination with 5-fluorouracil and leucovorin (nal-IRI+5-FU/LV) is the only approved therapy for metastatic PAC following gemcitabine-based therapy, based on the survival benefit demonstrated in the phase III NAPOLI-1 trial. Factors associated with long-term survival in this trial included age ≤65 years, Karnofsky performance status (KPS) ≥90, neutrophil-to-lymphocyte (N/L) ratio ≤5, carbohydrate antigen (CA) 19-9 <59-times the upper limit of normal (ULN), and no liver metastases. Using real-world data from studies conducted in Korea, Italy, and Germany, this review aims to assess the suitability of prognostic factors identified in the NAPOLI-1 trial nomogram. In these real-world studies, a high CA19-9 level and a low N/L ratio were associated with long-term survival in patients treated with nal-IRI+5-FU/LV. The impact of albumin levels, body mass index (BMI), liver metastasis, and KPS on survival identified from the NAPOLI-1 trial was confirmed in some real-world analyses but not consistently. Factors such as patient age and number of previous lines of treatment that were not identified in the NAPOLI-1 nomogram may be associated with long-term survival with nal-IRI+5-FU/LV in the real-world. In conclusion, this review has shown that while prognostic factors are useful for patient stratification, their predictive value on the efficacy of nal-IRI+5-FU/LV is low, thus this treatment may also result in long-term survival in patients with apparently unfavorable characteristics.